Computer-Based Information Services in Food Science and Technology: A Survey of Users Interests. (Information User Studies 16) - Sangarneswaran, S. V.; Chandran, Ranjita (Journal of Information and Knowledge, 1979)
It has been proposed to develop a computer-based information service at the National Information Centre for Food Science and Technology forming part of the Central Food Technology Research Institute (CFTRI) at Mysore. Before initiating the programme a users 'survey has been conducted to assess the users' acceptability of computer-based information services in food science and technology. It was found that in a nutshell majority of respondents conveyed their willingness to use the services.